EU-Azerbaijan Relations : Geopolitical aspects and Energy Security Cooperation - Hajiyeva, Hokuma; Garlick, Jeremy; Shakhanova, Gaziza; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis aims to do a thorough examination of the geopolitical context and cooperation in energy security in the relationship between the European Union (EU) and Azerbaijan. The goal of this master's thesis is to contribute to a more nuanced understanding of the dynamics of collaboration between Azerbaijan and the EU by using a geopolitical and energy security approach. The historical geopolitical elements that have shaped the evolution of EU-Azerbaijan ties will be examined in order to accomplish this aim. The strategic partnership between the European Union and Azerbaijan is shaped by contemporary geopolitical dynamics. This includes examination of global trends, present political circumstances, and regional crises. Investigations will also be conducted on the ways in which cooperation on energy security strengthens ties between the EU and Azerbaijan. Analyzing energy-related agreements, initiatives, and policies involving the EU and Azerbaijan as well as how they affect the two countries' broader diplomatic and strategic relations will be part of this. In addition, the main obstacles and chances for improving cooperation in the fields of geopolitics and energy security will be noted and examined. This might entail looking at possible areas for mutual benefit and progress as well as roadblocks to greater cooperation.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses